2002
DOI: 10.1111/j.1467-842x.2002.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Prevalence: Obesity, diabetes and associated cardiovascular risk factors among Torres Strait Islander people

Abstract: Objective:To describe the lifestyle‐related chronic disease and risk factor prevalence among Torres Strait Islander people of the Torres Strait and Northern Peninsula Area Health Service District and to compare this information with that available for the general Australian population. Methods:Voluntary community‐based screening for persons aged 15 years and older, including oral glucose tolerance test, anthropometry, health questionnaire, measurement of lipids and lipoprotein levels, blood pressure and urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 16 publications
5
74
1
Order By: Relevance
“…Renal disease, largely attributed to glomerulonephritis and type 2 diabetes, is a serious health problem in the Torres Strait and in Australian Aboriginal communities (Hoy, 1996;Leonard et al, 2002;AIHW, 2005). It is identified in major strategies as a priority health problem needing applied research into its causes and prevention (Torres Strait and Northern Peninsula Area Health Council, 1993;National Aboriginal and Torres Strait Islander Health Council, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal disease, largely attributed to glomerulonephritis and type 2 diabetes, is a serious health problem in the Torres Strait and in Australian Aboriginal communities (Hoy, 1996;Leonard et al, 2002;AIHW, 2005). It is identified in major strategies as a priority health problem needing applied research into its causes and prevention (Torres Strait and Northern Peninsula Area Health Council, 1993;National Aboriginal and Torres Strait Islander Health Council, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Voluntary adult (415 years of age) health screening was performed in 1996 in these two Torres Strait Island communities following an invitation from the communities to the regional public health unit (Leonard et al, 2002).…”
Section: Community Programsmentioning
confidence: 99%
“…In addition, there are important differences between the two ethnic groups which have an impact on health outcomes. Reported prevalence of high BMI and diabetes is higher among the population of Torres Strait Islanders (TSI) than Aborigines (8,9) , and there are also differences in reproductive outcomes. More than 25 % of Aboriginal and 15 % of TSI mothers, compared to less than 5 % of nonindigenous mothers in far north Queensland (FNQ), are less than 20 years of age.…”
Section: Nutrition Indigenous Womenmentioning
confidence: 99%
“…24 This study also found the incidence in the below 35 year old age group to still be relatively high at 5.3%. Another study used community based screening to find that obesity rates for Torres Strait Islanders were three times higher and diabetes rates six times higher than for other Australians 25 (Fig. 4).…”
Section: Dietmentioning
confidence: 99%